Strategi Pengembangan Manajemen Sumber Daya Manusia Dalam Menghadapi Masyarakat Ekonomi Asean - Rama Putra Haki; Ahmad Shobari; Syarifah Gustiawati (LP2M Sekolah Tinggi Ilmu Syariah Darul Falah Mataram, 2018)
This research aims to find the clear overview about the development strategy of human resource management in dealing with the ASEAN Economic Community (AEC) at PT. Goenoeng Poetri Lestari in Tasikmalaya. This is done considering it needs to develop a good development strategy of human resources management in accordance with broader market coverage like ASEAN. This research used descriptive-qualitative methods. The results of this research shows that social system method approach is utilized by PT. Goenoeng Poetri Lestari in their approach. Furthermore, the results of their SWOT analysis there are such as strength, it comes from their number of human resources that 95% employees who live in Gunung Putri area itself help company easier to mobilize; as their weakness, commonly most of their employees are newbie in their job experience; meanwhile the existence of PT. Goenoeng Poetri Lestari as the only one company in that area becomes their opportunity to develop easier; and last their threat comes from their inexperience human resources. It is worried that they cannot compete with AEC. In addition, the human resources development programs that was carried out by PT. Goenoeng Poetri Lestari are twice apprenticeship programs of the manpower goverment office and several small traingings for each fields.